STUDI EKOLOGI KEONG MAS (POMACEA CANALICULA L.) SEBAGAI BAHAN SUMBANGAN MATERI PEMBELAJARAN KONTEKSTUAL PADA MATA PELAJARAN BIOLOGI SMA DI OKU TIMUR - Riyanto Riyanto; Zukifli Dahlan; Adeng Slamet (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2015)
Abstract: This paper aims to inform the contribution from the research result of ecology study golden snail (Pomacea canalicula L.) in Belitang OKU Timur. Method used survey with descriptive pattern. This method described the data of survey result which obtained by researchers. Focus of observation is on biotic and abiotic components which affect the population of golden snail. This research result can contributed on learning activity process of senior high school student first grade concentric Mathematic and sciences, basic competence biology especially, 3.9 Analyzing data or information from various sources about ecosystem and all interaction occurred in it., 3.10 Analyzing data of environment changing and the impact to life., 4.9 Designing a chart of the interaction between the ecosystem components and food cycle held in an ecosystem and providing the results in various forms of media., 4.10 Solving environmental problems by designing wasted recycled products and preserving the environment. The contribution of ecology golden snail in OKU Timur research result is formed in lesson plan (RPP) for study material and student work sheet (LKPD). This research aimed to trigger biology teachers of high school in OKU Timur regency to find other example of the biology lesson based on local sample as well as sample of the contextual learning material taken from daily lives of high school student in OKU Timur. Â Keys Word: Ecology, Pomacea canalicula L . and Lesson Plans ( RPP )